2009
DOI: 10.1016/j.acvd.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of proximal isovelocity surface area (PISA) shape using three-dimensional echocardiography in a paediatric population with mitral regurgitation or ventricular shunt

Abstract: 3DE describes the true surface of the PISA shape. In a paediatric population with MR or VS, the PISA is rarely hemispherical but is more often prolate or oblate hemispheroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In one study involving 11 academic centres, the rate of "substantial agreement" among echocardiologists for distinction of severe from non-severe MR using EROA was only 38% 22). Other limitations of the two-dimensional color Doppler PISA technique, including geometric assumptions of the flow convergence zone, have become apparent from three-dimensional echocardiographic and cardiac magnetic resonance studies 30)31). The validity of using the standard PISA technique to quantitate predominantly mid-to-late systolic regurgitation characteristic of MVP is also in doubt.…”
Section: Role Of Rest Echocardiographymentioning
confidence: 99%
“…In one study involving 11 academic centres, the rate of "substantial agreement" among echocardiologists for distinction of severe from non-severe MR using EROA was only 38% 22). Other limitations of the two-dimensional color Doppler PISA technique, including geometric assumptions of the flow convergence zone, have become apparent from three-dimensional echocardiographic and cardiac magnetic resonance studies 30)31). The validity of using the standard PISA technique to quantitate predominantly mid-to-late systolic regurgitation characteristic of MVP is also in doubt.…”
Section: Role Of Rest Echocardiographymentioning
confidence: 99%
“…Several reports presented data on only a limited number of healthy control subjects, and some described findings in children from infants to teenagers with total sample sizes less than 50 subjects. 28,29,31 This makes it impossible to create size or age specific normal ranges. Because of the absence of a standardised methodology based on expert consensus to measure valvular gradients and severity of regurgitation in the paediatric population, all studies used different approaches.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Systems to classify mitral stenosis severity have been rarely reported, and when employed 10,12 different cut-off values have been used to define mild, moderate, and severe stenosis. For regurgitant lesions, variable echocardiographic views (four-chamber and/or parasternal views) [29][30][31] and parameters to evaluate disease severity (i.e. proximal isovelocity surface area or vena contracta) have been used.…”
Section: Methodological Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, it was recently shown that the true PISA is generally more hemi-elliptical than hemispherical, and that an erroneous assumption of spherical PISA underestimates the severity of MR (see Figure 1). 9 This is even more significant in those cases of functional MR. 9,10 Despite attempts to introduce corrections to the PISA formula, differences in orifice shape, size, and leaflet angle made strict formulae always inaccurate in the presence of non-circular lesions. 9,11,12 To minimize the effect of this limitation, cut-off values for severity grading are different in functional versus organic MR (≥0.2 cm 2 versus ≥0.4 cm 2 , respectively).…”
mentioning
confidence: 99%